2015
DOI: 10.1111/1754-9485.12333
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine and dexamethasone: a potentially dangerous combination for therapeutic pain injections

Abstract: Introduction: Targeted spinal steroid injections are effective in reducing back pain in selected patient populations and carry a small risk of significant adverse neurological outcomes. Recent recommendations are for the use of non-particulate steroid agents for all spinal injections to reduce the risk of neurovascular embolic adverse events. Many injections have used a combination of local anaesthetic agent with the steroid. At our institutions, we have recently observed interactions between ropivacaine and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…As such, the author advised that much attention be paid to the time- and concentration-dependent toxicity when dexamethasone is combined with ropivacaine 37. In agreement with previous results,38,39 in a preliminary animal experiment, we found that solutions of commonly used local anesthetics (bupivacaine, ropivacaine) in combination with nonparticulate dexamethasone sodium phosphate could crystallize, even in physiological pH (unpublished data). Therefore, the patient’s safety might be compromised when crystalliferous solution is unintentionally injected into the subarachnoid space or into the blood vessels.…”
Section: Discussionsupporting
confidence: 87%
“…As such, the author advised that much attention be paid to the time- and concentration-dependent toxicity when dexamethasone is combined with ropivacaine 37. In agreement with previous results,38,39 in a preliminary animal experiment, we found that solutions of commonly used local anesthetics (bupivacaine, ropivacaine) in combination with nonparticulate dexamethasone sodium phosphate could crystallize, even in physiological pH (unpublished data). Therefore, the patient’s safety might be compromised when crystalliferous solution is unintentionally injected into the subarachnoid space or into the blood vessels.…”
Section: Discussionsupporting
confidence: 87%
“…The vasoconstricting activity of ropivacaine (in contrast to the vasodilating effects of lidocaine and bupivacaine) poses a similar hazard to neural tissue [72,73]. As stated previously, ropivacaine mixed with DSP may lead to crystallization and unexpected risk for intravascular embolization [28].…”
Section: Local Anestheticsmentioning
confidence: 85%
“…Celestone Soluspan (Merck Sharp Dohme) combines insoluble (betamethasone acetate) and soluble (betamethasone sodium phosphate) corticosteroids. The rod-shaped crystals in this formulation are overall small (10-30 μm), but the largest measure 50 μm, and aggregates reach 100 μm [24,28].…”
Section: Macmahon Et Almentioning
confidence: 91%
See 1 more Smart Citation
“…Avoidance of particulate corticosteroids appears to be a safety measure that might eliminate the risk for embolization of an RMA, although the solubility of dexamethasone has recently been called into question when combined with ropivacaine but not with lignocaine or bupivacaine, leading to precipitation into non‐soluble particles [4‐6]. Importantly, avoidance of particulate corticosteroids does not preclude direct injury to the RMA.…”
Section: Case Scenariomentioning
confidence: 99%